2011
DOI: 10.1055/s-0031-1299901
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Controlled Trial of Two Nifedipine Extended Release Formulations in the Treatment of Essential Hypertension

Abstract: The aim of this study was to assess the pharmacodynamic equivalence of two different slow-release formulations of nifedipine (CAS-21829-25-4). In a prospective, controlled, double-blind clinical trial, 42 patients with essential hypertension (sitting diastolic blood pressure (DBP) 95-114 mmHg) underwent an initial washout, drug free period of 2 weeks, after which they were randomized to receive either 30 mg of nifedipine in the test preparation "XL" (Nifecard) or 30 mg of nifedipine in a reference formulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Thirty studies reported goal rates (i.e. achievement of a specific target BP, such as DBP 590 mmHg), but not other responder rates [De Roa et al 2007;Giles et al 2007;Hosohata et al 2007;Lacourciere et al 2007;Mahmud and Feely, 2007;Mancia et al 2007b;Mochizuki et al 2007;Saito et al 2007;Tobe et al 2007;Chrysant et al 2006;Neutel et al 2006;Papademetriou et al 2006;Lacourciere et al 2005;Sellin et al 2005;Smith et al 2005;Del Vecchio et al 2004;Leu et al 2004;Mourad et al 2004;Neutel et al 2004;Palatini et al 2004;Black et al 2003;Brunner and Laeis, 2003;Eguchi et al 2003;Pepine et al 2003a;Pepine et al 2003b;Phillips et al 2003;Deary et al 2002;Elliott et al 2002;Pivac et al 2002;Lacourciere et al 2001]. Goal rates were either for a combined SBP/DBP goal or individual SBP or DBP goals.…”
Section: Use Of Bp Goal Rates As Clinical Trial Endpointsmentioning
confidence: 99%
“…Thirty studies reported goal rates (i.e. achievement of a specific target BP, such as DBP 590 mmHg), but not other responder rates [De Roa et al 2007;Giles et al 2007;Hosohata et al 2007;Lacourciere et al 2007;Mahmud and Feely, 2007;Mancia et al 2007b;Mochizuki et al 2007;Saito et al 2007;Tobe et al 2007;Chrysant et al 2006;Neutel et al 2006;Papademetriou et al 2006;Lacourciere et al 2005;Sellin et al 2005;Smith et al 2005;Del Vecchio et al 2004;Leu et al 2004;Mourad et al 2004;Neutel et al 2004;Palatini et al 2004;Black et al 2003;Brunner and Laeis, 2003;Eguchi et al 2003;Pepine et al 2003a;Pepine et al 2003b;Phillips et al 2003;Deary et al 2002;Elliott et al 2002;Pivac et al 2002;Lacourciere et al 2001]. Goal rates were either for a combined SBP/DBP goal or individual SBP or DBP goals.…”
Section: Use Of Bp Goal Rates As Clinical Trial Endpointsmentioning
confidence: 99%